2023
DOI: 10.1002/aur.3022
|View full text |Cite
|
Sign up to set email alerts
|

Habituation of auditory responses in young autistic and neurotypical children

Patrick Dwyer,
Zachary J. Williams,
Svjetlana Vukusic
et al.

Abstract: Prior studies suggest that habituation of sensory responses is reduced in autism and that diminished habituation could be related to atypical autistic sensory experiences, for example, by causing brain responses to aversive stimuli to remain strong over time instead of being suppressed. While many prior studies exploring habituation in autism have repeatedly presented identical stimuli, other studies suggest group differences can still be observed in habituation to intermittent stimuli. The present study explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 121 publications
0
1
0
Order By: Relevance
“…While the precise mechanism of habituation is not fully characterized, the habituation of sensory responses to redundant stimulation has been widely documented (Megela & Teyler, 1979;Schoenen, 1996;Thompson & Spencer, 1966). Interestingly, cortical responses show no habituation in disorders involving sensory processing (e.g., migraine with aura, autism; (Dwyer et al, 2023;Harriott & Schwedt, 2014;Rauschel et al, 2016)), which work (albeit limited) has suggested is due to aberrant GABAergic signaling from interneurons (Palermo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While the precise mechanism of habituation is not fully characterized, the habituation of sensory responses to redundant stimulation has been widely documented (Megela & Teyler, 1979;Schoenen, 1996;Thompson & Spencer, 1966). Interestingly, cortical responses show no habituation in disorders involving sensory processing (e.g., migraine with aura, autism; (Dwyer et al, 2023;Harriott & Schwedt, 2014;Rauschel et al, 2016)), which work (albeit limited) has suggested is due to aberrant GABAergic signaling from interneurons (Palermo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%